Influência do polimorfismo genético Val16Ala-SOD2 e da matriz química do guaraná no estado oxidativo-inflamatório in vitro do cloridrato de ziprasidona - Duarte, Thiago (2019)
Antipsychotics (APs) are used to treat schizophrenia and other psychiatric disorders. Most of these medications have adverse effects causing obesity and metabolic changes associated with oxidative stress and inflammation. Studies have reported that Ziprasidone (ZIP), unlike other APs, can cause the same effects in an attenuated manner, as well as allergic responses. Currently, the cause of the effects triggered by ZIP is not well characterized and some patients do not respond satisfactorily to the treatment, perhaps due to the influence of genetic polymorphisms. The action of the Val16AlaSOD2 polymorphism causes a superoxide-hydrogen peroxide (S-HP) imbalance, which is involved with oxidative-inflammatory metabolism. Bioactive molecules present in foods such as xanthines and catechins have an anti-inflammatory and antioxidant effect that may influence the attenuation of the adverse effects triggered by this drug. In order to better understand this information, this study investigated the in vitro effect of ZIP on the oxidative-inflammatory response of immune cells by evaluating the potential influence of the Val16Ala-SOD2 polymorphism and the guarana chemical matrix in the form of three experimental designs. In the first, we analyzed the in vitro effect of ZIP on the oxidative-inflammatory response of RAW 264.7 macrophages exposed to different ZIP concentrations (18.5, 37.5, 75, 150, 300 μg / mL) using phytohemagglutinin (PHA) as a positive control inflammation and lithium (Li) as a negative control through its action on the rate of cell proliferation, cell cycle, modulation of oxidative markers related to immune response, modulation of proinflammatory and anti- inflammatory cytokines and modulation of the gene expression of these cytokines via the qRT-PCR technique. The second in vitro protocol was conducted using peripheral blood mononuclear cells (PBMCs) obtained from healthy donors bearing different Val16Ala-SOD2 polymorphism genotypes exposed to ZIP in 72h cell culture. The previously mentioned markers were then measured, including levels of lipoperoxidative markers and DNA damage. The third protocol evaluated the effect of the xanthine-catechin (XC-Mix) chemical matrix of guarana powder that presents bioactive molecules in the modulation of the oxidative-inflammatory response triggered by ZIP on RAW 264.7 macrophages. The first study showed that in non-activated macrophages exposed to ZIP, there was induction of inflammatory response represented by macrophage spreading, increased cell proliferation, elevated levels of oxidant molecules and pro-inflammatory cytokines, and reduction of the anti-inflammatory cytokine as well as regulation and gene expression of all cytokines. The second study demonstrated a possible pharmacogenomic action of the Val16Ala-SOD2 polymorphism where CMSPs linked to the AA genotype exposed to the ZIP showed an increase of the basal levels of H2O2 evidencing a possible genotoxic effect while PBMCs linked to the VV genotype showed high levels of proinflammatory cytokines. The third protocol showed that XC-Mix supplementation promoted a reduction effect on cell proliferation and decreased levels of inflammatory, oxidative and genotoxic markers, contributing to the modulation and increase of anti-inflammatory cytokine levels. All of the described results show, despite the methodological limitations, a possible influence of the polymorphism on the adverse effects triggered by the ZIP and that the chemical matrix of guarana powder can guarantee anti-inflammatory and antioxidant effects. The results become relevant in the psychiatric clinic by opening the possibility of personalizing antipsychotic therapy as well as stimulating research for the development of alternative methods for the treatment of associated metabolic disorders.